The IGF2/IGF1R/Nanog Signaling Pathway Regulates the Proliferation of Acute Myeloid Leukemia Stem Cells - Dan-dan Xu; Dan-dan Xu; Dan-dan Xu; Ying Wang; Peng-jun Zhou; Shu-rong Qin; Rong Zhang; Yi Zhang; Xue Xue; Jianping Wang; Xia Wang; Hong-ce Chen; et al. (Frontiers Media S.A., 2018)
Acute myeloid leukemia is an aggressive disease characterized by clonal proliferation and differentiation into immature hematopoietic cells of dysfunctional myeloid precursors. Accumulating evidence shows that CD34+CD38- leukemia stem cells (LSCs) are responsible for drug resistance, metastasis, and relapse of leukemia. In this study, we found that Nanog, a transcription factor in stem cells, is significantly overexpressed in CD34+ populations from patients with acute myeloid leukemia and in LSCs from leukemia cell lines. Our data demonstrate that the knockdown of Nanog inhibited proliferation and induced cell cycle arrest and cell apoptosis. Moreover, Nanog silencing suppressed the leukemogenesis of LSCs in mice. In addition, we found that these functions of Nanog were regulated by the insulin-like growth factor receptor (IGF1R) signaling pathway. Nanog overexpression rescued the colony formation ability of LSCs treated with picropodophyllin (PPP), an IGF1R inhibitor. By contrast, knockdown of Nanog abolished the effects of IGF2 on the colony formation ability of these LSCs. These findings suggest that the IGF2/IGF1R/Nanog signaling pathway plays a critical role in LSC proliferation.